2009
DOI: 10.1111/j.1600-0781.2009.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Reappraising the phototoxicity of tretinoin: a report of four controlled clinical trials

Abstract: The findings in these studies are consistent with previous studies of tretinoin in various formulations, and support the conclusion that tretinoin appears to be neither phototoxic nor photoallergenic in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…This was demonstrated by four randomized, controlled, prospective trials that were carried out in healthy volunteers. Two trials examined phototoxicity following 24 h exposure of 0.05% tretinoin gel under occlusion, and two examined photoallergenicity following a 3-week, 6-dose induction phase followed by challenge [24]. Similar results were observed with 0.1% tazarotene foam: the latter has a low potential for phototoxic or photoallergic reactions [25].…”
Section: Retinoidssupporting
confidence: 50%
“…This was demonstrated by four randomized, controlled, prospective trials that were carried out in healthy volunteers. Two trials examined phototoxicity following 24 h exposure of 0.05% tretinoin gel under occlusion, and two examined photoallergenicity following a 3-week, 6-dose induction phase followed by challenge [24]. Similar results were observed with 0.1% tazarotene foam: the latter has a low potential for phototoxic or photoallergic reactions [25].…”
Section: Retinoidssupporting
confidence: 50%
“…Local adverse effects of tretinoin treatment include the ‘retinoid reaction’, also known as ‘retinoid dermatitis’, as well as exaggerated photosensitivity at the beginning of the treatment. Results from four prospective, randomized, controlled trials in healthy volunteers showed that tretinoin is neither phototoxic nor photoallergenic 52 . Several strategies to diminish and/or prevent the adverse effects of tretinoin application have been suggested and can be summarized as follows:…”
Section: Clinical Efficacy and Safety Of Topical Retinoids In The Manmentioning
confidence: 99%
“…Results from four prospective, randomized, controlled trials in healthy volunteers showed that tretinoin is neither phototoxic nor photoallergenic. 52 Several strategies to diminish and ⁄or prevent the adverse effects of tretinoin application have been suggested and can be summarized as follows: Dosing related • Once daily application, in the evening • Less frequent application if moderate to severe irritation occurs, i.e. alternate days or three times a week • Possible concomitant application of 3% indomethacin and ⁄or 1% hydrocortisone to relieve the irritant reaction 53…”
Section: Adverse Effects Of Tretinoin Treatment -How Can They Be Dimimentioning
confidence: 99%
“…Several studies have suggested that they are neither phototoxic nor photoallergic in vivo . 22 In controlled studies, when skin is pretreated with tretinoin and irradiated with UV light, there is no effect on the minimal erythema dose, indicating that tretinoin has no phototoxic activity and lacks sunscreen properties as well. 8 …”
Section: Retinoidsmentioning
confidence: 99%
“…Several studies have suggested that they are neither phototoxic nor photoallergic in vivo. 22 In controlled studies, when skin is pretreated with tretinoin and irradiated with UV light, there is no effect on the minimal erythema dose, indicating that tretinoin has no phototoxic activity and lacks sunscreen properties as well. 8 Tretinoin (all-trans-retinoic acid) is a topical vitamin A derivative that binds to and activates the nuclear retinoic acid receptor RAR; it is derived from sequential oxidation of alltrans retinol and all-trans retinaldehyde.…”
Section: Retinoidsmentioning
confidence: 99%